Comparison of Physicochemical Properties of Noodles Fortified with Commercial Calcium Salts versus Calcium Citrate from Oyster Shells - Lin, Hong-Ting Victor; Chen, Guan-Wen; Chang, Ke-Liang Bruce; Bo, Yi-Jun; Sung, Wen-Chieh (Foods, 2023)
This study examined the physicochemical effects of the fortification of noodles with 0.25–1.00% (w/w) calcium salts, viz. calcium acetate, calcium carbonate, calcium citrate, and calcium lactate. Fortification with calcium citrate, calcium acetate, and calcium carbonate increased the pH and breaking force of the dried noodles. However, the fortification of noodles with any concentration of calcium did not increase the extent of elongation of the control raw noodles. The L* and b* values of the raw and dried noodle color increased with increasing concentrations of calcium salts, except for noodles with added calcium citrate. Fortification with calcium citrate yielded no significant influence on color, texture, adhesiveness, springiness, flavor, and overall scores for cooked noodles. Noodles fortified with 0.5% calcium citrate made from oyster shells were compared with a control sample of noodles and noodles fortified with commercially available calcium citrate. The particle size of the calcium citrate made from oyster shells (258 nm) was smaller than that of the purchased calcium citrate (2631 nm). Noodles fortified with calcium citrate made from oyster shells showed no significantly difference compared to noodles fortified with commercially available calcium citrate. These results suggest that calcium citrate made from oyster shells may be used as the additive of choice for the manufacture of calcium-fortified noodles.